The relevance of John Dewey’s pragmatism for educational innovation in contemporary Vietnam - Kien Pham Thi (Cogent Education)
In the current era of global integration, and the fourth industrial revolution requires the education system to transform and combine traditional education with online education. Therefore, educational innovations are being implemented globally to meet the increasing demands of the modern labor market. However, Vietnamese education faces many challenges in innovation, such as the curriculum being too theoretical and lacking practicality. These teaching methods do not encourage creative and critical thinking, and unequal access to education exists between regions. Dewey’s philosophy emphasizes experiential education, where students learn through practical experiences, critical thinking, and problem-solving instead of passively absorbing knowledge. These ideas are consistent with current educational reforms in Vietnam, especially in transitioning from traditional education to an active learning model, developing creative thinking, and strengthening the connection between education and real life, technology, AI, and Big Data, and careers. Their combination is intertwined, creating a powerful synergy in innovation and success for Vietnam education today.